Vitamin K2 supplementation blocks the beneficial effects of IFN-α-2b administered in the early stages of liver cancer development in rats - Vera, Marina Cecilia (2019)
Objective: Vitamin K2, which is present in dairy products and has been recommended as a micronutrient supplement in humans, contains anticancer properties. Interferon (IFN)-α-2b administered during development of hepatic preneoplasia decreased both number and volume percentage of altered hepatic foci (AHF) by increasing apoptosis in the foci. The aim of this study was to evaluate the effects of IFN-α-2b treatment supplemented with vitamin K2 in the early stages of liver cancer development in rats. Methods: Adult male Wistar rats were subjected to a two-phase model of hepatocarcinogenesis (initiated-promoted [IP] group). Animals were divided into four groups: untreated (IP), IP treated with IFN-α-2b (6.5 × 105 U/kg), IP treated with vitamin K2 (10 mg/kg), and IP treated with both compounds. Results: The study results demonstrated that vitamin K2 blocked IFN-α-2b–induced reduction in size and volume of the altered hepatic foci and inhibited IFN-α-2b–induced apoptosis. Its inhibition of IFN-α-2b–induced apoptosis was mediated by increased levels of total hepatic Bcl-2 in rat preneoplastic livers. Conclusion: These findings demonstrate that supportive vitamin supplements or therapies are not always safe because they could put the life of patients treated with IFN-α-2b at risk.